Internet gaming disorder and the alternative five factor personality model: a study in a Spanish community sample - Anton Aluja; Oscar García; Ferran Balada; Neus Aymamí; Luis F. García (Current Issues in Personality Psychology)
Background This study was designed to examine the prevalence and relationships between the Internet gaming disorder (IGD) behaviors, suggested by the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), and personality traits.